Comprehensive metabolome and transcriptome analyses demonstrate divergent anthocyanin and carotenoid accumulation in fruits of wild and cultivated loquats - Su, Wenbing; Zhu, Changqing; Fan, Zhongqi; Huang, Mingkun; Lin, Han; Chen, Xiuping; Deng, Chaojun; Chen, Yongping; Kou, Yidan; Tong, Zhihong; Zhang, Yaling; Xu, Changjie; et al. (Frontiers in Plant Science, 2023)
Eriobotrya is an evergreen fruit tree native to South-West China and adjacent countries. There are more than 26 loquat species known in this genus, while E. japonica is the only species yet domesticated to produce fresh fruits from late spring to early summer. Fruits of cultivated loquat are usually orange colored, in contrast to the red color of fruits of wild E. henryi (EH). However, the mechanisms of fruit pigment formation during loquat evolution are yet to be elucidated. To understand these, targeted carotenoid and anthocyanin metabolomics as well as transcriptomics analyses were carried out in this study. The results showed that β-carotene, violaxanthin palmitate and rubixanthin laurate, totally accounted for over 60% of the colored carotenoids, were the major carotenoids in peel of the orange colored 'Jiefangzhong' (JFZ) fruits. Total carotenoids content in JFZ is about 10 times to that of EH, and the expression levels of PSY, ZDS and ZEP in JFZ were 10.69 to 23.26 folds to that in EH at ripen stage. Cyanidin-3-O-galactoside and pelargonidin-3-O-galactoside were the predominant anthocyanins enriched in EH peel. On the contrary, both of them were almost undetectable in JFZ, and the transcript levels of F3H, F3'H, ANS, CHS and CHI in EH were 4.39 to 73.12 folds higher than that in JFZ during fruit pigmentation. In summary, abundant carotenoid deposition in JFZ peel is well correlated with the strong expression of PSY, ZDS and ZEP, while the accumulation of anthocyanin metabolites in EH peel is tightly associated with the notably upregulated expressions of F3H, F3'H, ANS, CHS and CHI. This study was the first to demonstrate the metabolic background of how fruit pigmentations evolved from wild to cultivated loquat species, and provided gene targets for further breeding of more colorful loquat fruits via manipulation of carotenoids and anthocyanin biosynthesis.